(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the issues of ensuring cybersecurity in military activities. The increasing complexity of cyber threats and the increasing number of attacks on military infrastructure pose new challenges for the modern army. The authors point to the combination of a strategic approach, technical means, legal and regulatory framework and human resources as the main factors in ensuring military cybersecurity.